Spectroscopic Study of Long Period Eclipsing Binary 32 Cygni - Mun-Suk Chun (Journal of Astronomy and Space Sciences, 1992)
Spectra of the ζAurigae type eclipsing binary system 32 Cygni were taken at the Asiago Observatory. Using the Gaussian fitting method we can estimate the radial velocity and equivalent widths of some metalic lines.